Contextualization in Pentecostalism: A Multicultural Perspective - Anderson, Allan Heaton (International bulletin of mission research, 2017)
This article begins with discussing contextualization, what it is and is not, and why it is an important concept to understand in the practice and theology of Christian mission. Then it suggests that Pentecostalism has a fairly good record of contextualizing its message and mission, and explains why. Pentecostalism, through its offer of the power of the Spirit to enable every believer to witness to the ends of the earth, provides a contemporary example of the contextual flexibility of Christian mission in proclamation and practice. Finally, the article looks at a well-known case study of Pentecostal contextualization in South Korea, showing both its strengths and its weaknesses.